Kinetic and products of C3H3 and C4H2 reaction: theoretical and computational study - Antonius Indarto (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2011)
The formation of first aromatic ring was suggested to be a crucial step of the PAHs and soot growth mechanism. In general, four-, five-, six-, or seven-membered ring molecules could be formed by the addition reaction of two hydrocarbon molecules resulted from many different pathways. Small hydrocarbon molecules with numerous concentrations during combustion/pyrolysis are suspected to play an important role. Propargyl radical (•C3H3) and butadiene (C4H2) have been chosen as the initial reactants in this discussion, since they are found at relatively high concentrations in flame experiments to examine the above particular reaction. Following initial addition mechanisms, their adduct intermediate can form a ring molecule and undergo subsequent rearrangement. All possible molecular structures were considered and the viability of each channel was assessed through a “RRKM + master equation” kinetic study. This study is an attemp and example to develop and apply molecular computational method for solving problems in the chemical engineering.Keywords: reaction kinetic, ab-initio calculation, RRKM theory, unimolecular reaction, propargyl, butadiene.AbstrakReaksi pembentukan cincin aromatic pada senyawa hidrokarbon merupakan mekanisme awal terpenting dari pembentukan Polisiklik Aromatik Hidrokarbon (PAH) dan jelaga karbon. Secara umum, senyawa hidrokarbon dengan cincin berjumlah empat, lima, enam, atau tujuh dapat dibentuk oleh reaksi gabungan dua molekul hidrokarbon. Molekul hidrokarbon dengan jumlah atom karbon rendah akan memainkan peranan penting ditinjau dari besarnya konsentrasi senyawa ini saat pembakaran/pirolisis. Dalam diskusi ini, reaksi propargil radikal (•C3H3) dan butadiena (C4H2) digunakan sebagai studi kasus karena konsentrasinya yang relatif tinggi dalam percobaan laboratorium dengan menggunakan bunsen. Secara garis besar, reaksi pembentukan rantai lingkar (cincin) dapat tercapai baik secara langsung setelah reaksi adisi atau melalui penataan ulang molekul. Berbagai struktur molekul dan mekanisme yang mungkin ada dalam reaksi ini akan dianalisis melalui studi kinetika